2017
DOI: 10.1039/c7cc01042g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced single-ion magnetic and ferroelectric properties of mononuclear Dy(iii) enantiomeric pairs through the coordination role of chiral ligands

Abstract: The structures and properties of two mononuclear Dy(iii) enantiomeric pairs were dramatically controlled by crystallization temperature; the enantiomeric pair with coordinated chiral N,N'-donor ligands exhibits enhanced single-ion magnetic, ferroelectric and chiroptical properties with respect to the other one with protonated chiral N,N'-donor ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…It should be noted that, these complexes are not all square‐antiprism coordinated; some of them are significantly distorted and fall in other geometries like bicapped trigonal prism, or dodecahedron . This deviation introduces transverse anisotropy and leads to a faster magnetic relaxation .…”
Section: Lanthanide Simsmentioning
confidence: 87%
“…It should be noted that, these complexes are not all square‐antiprism coordinated; some of them are significantly distorted and fall in other geometries like bicapped trigonal prism, or dodecahedron . This deviation introduces transverse anisotropy and leads to a faster magnetic relaxation .…”
Section: Lanthanide Simsmentioning
confidence: 87%
“…Very interestingly, the research on homochiral molecular magnets has been highly valued, mainly because they can exhibit a magnetochiral dichroism (MChD) effect, which usually requires chirality and a strong magneto-optical Faraday effect corresponding to magnetic circular dichroism (MCD). , These magneto-optical materials themselves may be used in optical current transformer, magneto-optical switches, magneto-optical isolators, and fiber magneto-optical sensors. In addition, chiral molecular magnets may be attached with ferroelectric properties due to crystallization in a polar space group, becoming multiferroic molecular materials, or attached with second-order nonlinear optical activity due to crystallization in a noncentral symmetric space group, becoming magnetic-nonlinear optical multifunctional molecular materials. However, few homochiral SMMs have been reported, and the chirality of most SMMs is derived from N -donor ligands; , unfortunately, most homochiral SMMs require an external dc field to exhibit good magnetic relaxation properties. Moreover, homochiral SMMs with a strong magneto-optical Faraday effect have not been well developed. Recently, we adopted (−)/(+)-3-trifluoroacetyl camphor ( l -Htfc/ d -Htfc) acting as the chiral ligand to construct enantiomerically pure Dy­(III) dinuclear complexes, [Dy 2 ( l -tfc) 4 (chp) 2 (MeOH) 2 ] ( l - 1 ) (Hchp = 6-chloro-2-hydroxypyridine) and [Dy 2 ( d -tfc) 4 (chp) 2 (MeOH) 2 ] ( d - 1 ), which show ferromagnetic coupling and perform good zero field SMM properties; especially, they display a strong magneto-optical Faraday effect at room temperature.…”
Section: Introductionmentioning
confidence: 95%
“…In multifunctional materials based on coordination compounds, chirality can be spawn by using enantiomerically pure ligands (Amouri and Gruselle, 2008 ; Pinkowicz et al, 2015 ). The inherent chirality of the ligand may introduce additional functions to coordination compounds with interesting magnetic properties such as magnetochiral dichroism (MChD) effect (Rikken and Raupach, 1997 , 2000 ; Train et al, 2008 , 2011 ), second harmonic generation (SHG) (Bogani et al, 2006 ; Train et al, 2009 ), and ferroelectric properties (Wang et al, 2012 ; Li et al, 2017 ). It has been recently shown that mononuclear tris(β-diketonate) Dy III complexes containing a N,N-bidentate chelate aromatic ligand, such as 2,2′-bipyrimidine and 1,10-phenanthroline derivatives, as well as Dy 2 dinuclear complexes containing bis(didentate) bridging ligands connecting two tris(β-diketonate) Dy III moieties, such as 2,2'-bipyrimidine and 2,2'-bipyrimidine-N-oxide, exhibit Single-Molecule Magnet (SMM) behavior at zero field with significant thermal energy barriers ( U eff ) (Chen et al, 2011 , 2012 ; Wang et al, 2013 ; Tong et al, 2015 ; Sun et al, 2016 ; Yu et al, 2016 ; Cen et al, 2017 ; Díaz-Ortega et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%